DEVELOPING LISTENING FOR GENERAL COMMUNICATION COURSEBOOK FOR THE FIRST SEMESTER STUDENTS OF STKIP SILIWANGI BANDUNG - Lilis Suryani; Ningtyas Orilina Argawati (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2017)
AbstractListening is one of compulsory subjects for the students of English education study program of STKIP Siliwangi Bandung. It is taught at the first semester as a basic for the students to enhance others skills, such as speaking, reading, and writing. In fact, the students face problems in learning listening and it makes the objectives of learning do not achieve well. So, this research is aimed at creating listening course book to help the students learn effectively. This research focuses on listening for general communication. The research employed Research and Development. This method is divided into three parts; introductional study covers need analysis, literature review, proposal arrangements, and prototype;product developmentcovers materials arrangement and course book arrangement;and testinginvolves validation from expert, and revision. The subject of the research is the first semester students of English education study program of STKIP Siliwangi Bandung. The instruments used were interview and questionnaire. Interview was conducted to gather the data related with the themes used in the course book in every unit. There were six themes obtained through the interview. Then the themes chosen were developed based on the material guideline composed by the researcher in the previous research which cover macro and micro skill. Next is validation by three experts using questionaire. The revison covered the content, display and language, then the test was re-taken to gather the feasible of the coursebook. From the computation, the mean score of content hit the precentage of 79.17, while display was 77.78 and language was 77.5. from the resut, the researchers could assume that the course book was feasible and ready to use in teaching and learning of Listening for General Communication. Key words: listening for general communication, course book. R & D.